Life satisfaction in emerging adulthood: a longitudinal study of social support, resilience, and gender differences - Hanımoğlu, Egemen (Frontiers in Psychology, 2025)
BackgroundEmerging adulthood (ages 18–29) is a critical developmental period characterized by significant psychological and social transitions. While social support and psychological resilience have been consistently associated with wellbeing, their longitudinal associations with life satisfaction remain underexplored. Moreover, the potential moderating role of gender in these relationships is underrepresented in the existing literature, highlighting a gap this study seeks to address.ObjectivesThis study examines the longitudinal associations between social support and life satisfaction, investigates whether psychological resilience accounts for these associations, and explores the potential moderating role of gender over time. By employing a multi-wave design, it seeks to provide a nuanced understanding of how these psychological resources are interrelated across time.MethodsA total of 566 emerging adults (50.7% female, 49.3% male) participated in this three-wave longitudinal study conducted over 1 year with six-month intervals (T1, T2, T3). Structural Equation Modeling (SEM) was used to test direct and indirect effects of social support on life satisfaction through psychological resilience. Multi-group SEM and chi-square difference tests were conducted to assess gender differences in the proposed pathways.ResultsHigher levels of social support at T1 were significantly associated with greater life satisfaction at T2 and T3 (β = 0.22, p < 0.01). Psychological resilience was found to partially account for this association (indirect effect: β = 0.25, p < 0.001), suggesting that resilience may function as a linking factor between social support and subsequent wellbeing. Gender appeared to moderate these associations (Δχ2 = 16.27, p < 0.001), with stronger paths observed among women—particularly in the association between social support and resilience.ConclusionThis study contributes longitudinal evidence indicating that social support is positively associated with life satisfaction, both directly and through its associations with psychological resilience. The gender-specific patterns observed in the findings underscore the relevance of developing mental health interventions that consider individual differences in support utilization and coping strategies. These insights may inform theoretical frameworks and guide practical efforts to enhance wellbeing across diverse populations. Future research is encouraged to examine these associations across varying cultural and demographic contexts to further refine theoretical models and improve intervention strategies.